2019
DOI: 10.1016/j.jid.2019.01.023
|View full text |Cite
|
Sign up to set email alerts
|

ZAG Regulates the Skin Barrier and Immunity in Atopic Dermatitis

Abstract: Adipokines modulate immune responses and lipid metabolism in allergic disease; however, little is known about their role in the skin barrier and atopic dermatitis (AD). We identified ZAG, an adipokine that regulates lipid mobilization, as a biomarker for AD. ZAG levels were consistently decreased in sera, T cells, and skin in human AD patients compared with healthy controls. ZAG was primarily detected in the stratum corneum along with FLG and LOR. Knockdown of ZAG with short hairpin RNA resulted in decreased F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 43 publications
(51 reference statements)
2
23
0
Order By: Relevance
“…Also, we detected a decreased expression of AZGP which is correlated with abnormalities in lipid metabolism. Recently, AZGP has been suggested to be a possible biomarker and therapeutic target in AD 49 . In our study, alteration in lipid metabolism has been highlighted by lower expression of PLB1, PLBD2, PLD3, DHCR7, C11orf54, ACPP, ANXA7 and NPM1.…”
Section: Discussionmentioning
confidence: 52%
“…Also, we detected a decreased expression of AZGP which is correlated with abnormalities in lipid metabolism. Recently, AZGP has been suggested to be a possible biomarker and therapeutic target in AD 49 . In our study, alteration in lipid metabolism has been highlighted by lower expression of PLB1, PLBD2, PLD3, DHCR7, C11orf54, ACPP, ANXA7 and NPM1.…”
Section: Discussionmentioning
confidence: 52%
“…ZAG is widely found in human body uids, with carrier protein, ribonuclease activity and other functions 9 . In recent years, many studies have shown that ZAG has function of regulating immunity, cell adhesion, and regulating of melanin production 13,14 . Some studies [15][16][17] also pointed out that ZAG can be used as a biomarker for the early diagnosis of cancer, and its can participate in regulating tumor cell proliferation and glucose metabolism 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The monomers bind keratin filaments and finally form the scaffold of corneocytes. In a recent work, the protein zinc α-2-glycoprotein (ZAG) produced by adipocytes and keratinocytes of the skin was identified as a positive regulator of filaggrin expression [ 15 ]. ZAG, which is also proclaimed as a biomarker for AD, was also able to positively affect the levels at the epidermal cytokine thymic stromal lymphopoietin (TSLP) in this study.…”
Section: Effects Of a Basic Skin Therapy As A Primary Prevention Measurementioning
confidence: 99%